Effect of Long-Term Vinasse Application on Physico-chemical Properties of Sugarcane Field Soils - Ze-Pu Jiang; Yang-Rui Li; Guang-Po Wei; Qing Liao; Tian-Ming Su; Yan-Cheng Meng; Hai-Ying Zhang; Chang-Yan Lu (Sugar Tech, 2012)

Docetaxel-loaded liposomes: preparation, pH sensitivity, Pharmacokinetics, and tissue distribution - Hong Zhang; Rui-ying Li; Xia Lu; Zhen-zhen Mou; Gui-mei Lin (Journal of Zhejiang University-SCIENCE B, 2012)

Molecular characterization of Chinese Hop stunt viroid isolates reveals a new phylogenetic group and possible cross transmission between grapevine and stone fruits - Zhixiang Zhang; Ying Zhou; Rui Guo; Lingxiao Mu; Yuanai Yang; Shifang Li; Hongqing Wang (European Journal of Plant Pathology, 2012)

MicroRNAs in trees - Ying-Hsuan Sun; Rui Shi; Xing-Hai Zhang; Vincent L. Chiang; Ronald R. Sederoff (Plant Molecular Biology, 2012)

Construction of self-cloning, indigenous wine strains of Saccharomyces cerevisiae with enhanced glycerol and glutathione production - Rui-Ying Hao; Yan-Lin Liu; Zhao-Yue Wang; Bo-run Zhang (Biotechnology Letters, 2012)

Screening for significant atherosclerotic renal artery stenosis with a regression model in patients undergoing transradial coronary angiography/intervention - Li-jin Pu; Ying Shen; Rui-yan Zhang; Qi Zhang; Lin Lu; Feng-hua Ding; Jian Hu; Zheng-kun Yang; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2012)

Synthesis and studies on antidepressant activity of 2′,4′,6′-trihydroxychalcone derivatives - Xin Sui; Ying-Chun Quan; Yue Chang; Rui-Peng Zhang; Yin-Feng Xu; Li-Ping Guan (Medicinal Chemistry Research, 2012)

Effects of Danggui Buxue Tang, a traditional Chinese herbal decoction, on high glucose-induced proliferation and expression of extracellular matrix proteins in glomerular mesangial cells - Hao-Liang Ke; Ying-Wen Zhang; Bi-Fa Zhou; Rui-Tang Zhen (Natural Product Research, 2012)

Determination of Geometrical and Structural Representative Volume Elements at the Baihetan Dam Site - Wen Zhang; Jian-ping Chen; Chang Liu; Rui Huang; Ming Li; Ying Zhang (Rock Mechanics and Rock Engineering, 2012)

Development of SSR markers for typing cultivars in the mushroom Auricularia auricula-judae - Rui Ying Zhang; Dan Dan Hu; Jin Gang Gu; Qing Xiu Hu; Xue Mei Zuo; He Xiang Wang (Mycological Progress, 2012)

Chemical composition and antioxidant activities of extracts from Apocyni Veneti Folium - Sui-Hong Yan; Ying-Yong Zhao; Hai-Song Zeng; Yongmin Zhang; Rui-Chao Lin; Wen-Ji Sun (Natural Product Research, 2012)

Calculating the Anisotropic Permeability of Porous Media Using the Lattice Boltzmann Method and X-ray Computed Tomography - Yuan Gao; Xiaoxian Zhang; Pratap Rama; Ying Liu; Rui Chen; Hossein Ostadi; Kyle Jiang (Transport in Porous Media, 2012)

Metagenomic analysis of DNA viruses in a wastewater treatment plant in tropical climate - Hideyuki Tamaki; Rui Zhang; Florent E. Angly; Shota Nakamura; Pei‐Ying Hong; Teruo Yasunaga; Yoichi Kamagata; Wen‐Tso Liu (Environmental Microbiology, 2012)
Summary Viruses have been detected in the different stages of wastewater treatment plants (WWTPs) at concentrations of 10 8 –10 10 ml −1 of virus‐like particles (VLPs), 10–1000 times higher than in natural aquatic environments, suggesting that WWTPs can be considered as an important reservoir and source of viruses. This study revealed novel diversity and function with the DNA viral communities in the influent, activated sludge, anaerobic digester, and effluent of a domestic WWTP using metagenomics. WWTP was a very specific environment, with less than 5% of the > 936 000 metagenomic sequences obtained (∼70–119 Mbp per sample) similar to sequences present in other environmental viromes. Many viruses found in the WWTP were novel, resulting in only 82% were shared. These data suggested that VLPs of most viral types could be present between 1 and 30 days in the process before they were discharged. Viruses in WWTP and the discharged ones can have potential impacts on the functioning of the wastewater treatment system and on the dynamics of microbial community in the surrounding aquatic environments respectively.